2008
DOI: 10.1128/jcm.00625-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 11 Common Viral and Bacterial Pathogens Causing Community-Acquired Pneumonia or Sepsis in Asymptomatic Patients by Using a Multiplex Reverse Transcription-PCR Assay with Manual (Enzyme Hybridization) or Automated (Electronic Microarray) Detection

Abstract: Community-acquired pneumonia (CAP) and sepsis are important causes of morbidity and mortality. We describe the development of two molecular assays for the detection of 11 common viral and bacterial agents of CAP and sepsis: influenza virus A, influenza virus B, respiratory syncytial virus A (RSV A), RSV B, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella pneumophila, Legionella micdadei, Bordetella pertussis, Staphylococcus aureus, and Streptococcus pneumoniae. Further, we report the prevalence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 42 publications
4
61
0
2
Order By: Relevance
“…Furthermore, even when viruses are detected by lower respiratory tract sampling, contamination from the upper airways may have occurred. Conversely, a study using PCR found that asymptomatic nasopharyngeal carriage in adults was common for Staphylococcus aureus (9.1%) and Streptococcus pneumoniae (6.8%), but absent for the four viruses tested: influenza virus A, influenza virus B, respiratory syncytial virus A and respiratory syncytial virus B [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even when viruses are detected by lower respiratory tract sampling, contamination from the upper airways may have occurred. Conversely, a study using PCR found that asymptomatic nasopharyngeal carriage in adults was common for Staphylococcus aureus (9.1%) and Streptococcus pneumoniae (6.8%), but absent for the four viruses tested: influenza virus A, influenza virus B, respiratory syncytial virus A and respiratory syncytial virus B [43].…”
Section: Discussionmentioning
confidence: 99%
“…RSV is ubiquitous and nearly all children are infected by 2 years of age or following two RSV seasons, and LRTIs due to RSV are a leading cause of hospitalisation during the first year of life [7,[22][23][24]. However, only a subset of the infected children develops severe disease [8,[23][24][25][26][27]. In addition to the variability in severity among different RSV seasons, a number of host-related characteristics may increase the risk of hospital admission rates for RSV-induced LRTI in young children [8,[23][24][25][26][27][28].…”
Section: Rsv and Respiratory Infectionsmentioning
confidence: 99%
“…Strictly speaking, the high sensitivity of these tests may complicate clinical interpretation, as the presence of small amounts of viral targets may not necessarily prove their pathogenetic role. However, prospective case-control studies in asymptomatic and symptomatic young children have shown that a positive RSV test result is almost always of clinical relevance, independent of viral quantity [24,25].…”
Section: Rsv and Respiratory Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daxboeck et al (8) stated that transient asymptomatic carriage of M. pneumoniae resulted from the persistence of the pathogen after previous disease and from infections during incubation periods. Asymptomatic healthy children act as carriers of M. pneumoniae at a rate of 0z-2.2z (12)(13)(14); however, because the detection of M. pneumoniae DNA in throat swabs is not necessarily indicative of a causative role of the pneumonic pathogen, an infectious state is often difficult to distinguish from carriage during the acute phase. Given the high positive predictive value of the LAMP assay in this study, the use of antimycoplasma therapy in LAMP-positive cases diagnosed with pneumonia may be reasonable.…”
mentioning
confidence: 99%